2019
DOI: 10.1002/ecs2.2548
|View full text |Cite
|
Sign up to set email alerts
|

Using multiple data sources to investigate foraging niche partitioning in sympatric obligate avian scavengers

Abstract: As carrion feeders competing for a limited and ephemeral resource, avian scavengers are ideal model organisms to study mechanisms of niche partitioning. Previous work has focused on observations of species' interactions at carcasses, and although fruitful, the inclusion of behavior beyond that at carcasses, such as movement patterns, could yield a more comprehensive understanding of mechanisms of foraging niche partitioning. Our goal was to assess how differences in physiological, morphological, and social cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
(120 reference statements)
1
15
0
Order By: Relevance
“…These species are well known to be highly efficient scavengers (Sebasti an-Gonz alez et al 2016, Mateo-Tom as et al 2017, Morales-Reyes et al 2017. Vultures specialize in the consumption of carrion Houston 2004, Cort es-Avizanda et al 2014), and they can outcompete other vertebrates for carrion resources (Byrne et al 2019). Other species, such as mesopredators, can also monopolize carcasses in human dominated landscapes devoid of large mammalian predators (DeVault et al 2011, Buechley andS ßekercio glu 2016), whereas bear species Ursus spp.…”
Section: Introductionmentioning
confidence: 99%
“…These species are well known to be highly efficient scavengers (Sebasti an-Gonz alez et al 2016, Mateo-Tom as et al 2017, Morales-Reyes et al 2017. Vultures specialize in the consumption of carrion Houston 2004, Cort es-Avizanda et al 2014), and they can outcompete other vertebrates for carrion resources (Byrne et al 2019). Other species, such as mesopredators, can also monopolize carcasses in human dominated landscapes devoid of large mammalian predators (DeVault et al 2011, Buechley andS ßekercio glu 2016), whereas bear species Ursus spp.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Turner et al (2017) found that carrion detection times were 50% larger in habitats with more vegetation cover, especially during the warm season. In addition, vegetation cover can influence species composition, with species with developed sense of smell appearing in areas with more cover rather than species more dependent on visual cues (Byrne et al, 2019). Also, birds are expected to occur more often in open than in dense forest areas, where mammals tend to be more abundant (Pardo-Barquín et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that body size differences among sympatric bird species facilitate community coexistence (Leyequién et al, 2007). Therefore, we consider that the differences in the use of ridge crests help form of niche divergence adopted by sympatric mammals and birds that allows the coexistence of related species (Byrne et al, 2019;Cui et al, 2008;Namgail et al, 2004;Wei et al, 1999). An et al (2009) suggested that the current geographic range of T. tibetanus has been influenced by the most recent large-scale glaciations on the QTP in and before the Pleistocene.…”
Section: Discussionmentioning
confidence: 92%
“…Habitat partitioning based on ridge crests serves to reduce both interference and competition, facilitating the coexistence of ecologically similar species. Habitat partitioning is a widespread form of niche divergence adopted by sympatric mammals and birds that allows the coexistence of related species (Byrne et al, 2019 ; Cui et al, 2008 ; Namgail et al, 2004 ; Wei et al, 1999 ). An et al ( 2009 ) suggested that the current geographic range of T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation